Persistent Magma‐Rich Waves Beneath Mid‐Ocean Ridges Explain Long Periodicity on Ocean Floor Fabric - S. J. Sim (Geophysical Research Letters)
Abstract The ocean floor makes up the majority of the Earth's surface and yet, its geomorphology is not fully understood. Recent debate has focused on whether sea level changes—driven by Milankovitch glacial cycles—generate the abyssal hill fabric of the ocean floor by modulating mid‐ocean ridge magma supply. However, periodicities longer than Milankovitch cycles are prominent in the ocean bathymetry. Using crustal thickness estimates from two‐phase flow simulations of ridge magma transport, I show that persistent melt‐rich porosity waves could be responsible for the ocean floor fabric at periods of 100 kyr and longer, except in the case of fast‐spreading ridges. For periods longer than 100 kyr, spectral energy is notably present at large mantle permeabilities regardless of spreading rates. Therefore, two‐phase flow models can provide constraints on elusive mantle parameters such as permeability and viscosity when directly linked to the ocean floor fabric produced.